Potensi Produk Organik Kabupaten Lumajang: Studi Komoditas Salak - Soejono, Djoko; Arum, Ayu Puspita; Utami, Ratih Apri; Amam, Amam (Universitas Galuh, 2025)
Lumajang District plans to develop the development of the organic agricultural sector with the aim of maintaining the balance of nature for the sustainability of agriculture in the future. Salak is one of the leading commodities of Lumajang District with the potential for developing an organic system. The purpose of this study was to determine the mapping of potential, implementation of agribusiness systems, economic value, and strategies for developing organic products of salak commodities in Lumajang District. The location of the study was in Lumajang District, the sampling method was purposive sampling and snowball sampling. Data collection used observation, interview, and Focus Group Discussion (FGD) methods. The types of data used in the study were primary and secondary data. The results of the study showed that organic salak commodities were very suitable for development in Candipuro, Gucialit, Jatiroto, Kedungjajan, Klakah, Kunir, Padang, Pasirian, Pasrujambe, Randuagung, Ranuyoso, Senduro, Sukodono, Tempeh, Tempusari, and Yosowilangun Districts. Various obstacles in implementing the organic salak plant agribusiness system include: a) seeds from propagation from farmers' gardens are not/have not been guaranteed in quality; b) raw materials for making natural fertilizers and pesticides are not guaranteed to be free from chemical contamination; c) cultivation, harvesting, and post-harvest equipment are also used for inorganic activities; d) there are no special packaging facilities; e) market segmentation has not been formed because consumers do not differentiate between organic and inorganic products; and f) weak institutional management of farmer groups and farmer group associations (gapoktan). Revenue per Cost (R/C) analysis of organic snake fruit farming business is 1.55. The priority choice of organic snake fruit product development strategy is strengthening farmer institutions..